BENTUK PENGEMBANGAN SDM DI LEMBAGA PENDIDIKAN ISLAM : Urgensi Pengembangan Sumber Daya Manusia Dalam Pendidikan - Kardina Engelina Siregar (AL-MA'LUMAT : JURNAL ILMU-ILMU KEISLAMAN, 2023)
The existence of human resources in an Islamic Education Institution plays a very important role in realizing the vision, mission, goals and objectives of an Islamic Education Institution. So it requires maximum management, development and empowerment to create a quality Islamic Education Institution. In management science there is study material on forms of HR development for Islamic Education Institutions, which aims to ensure that Islamic Education Institutions carry out their role in improving the quality of education. As we all know, the stages that management goes through in general are POAC (Planning, Organizing, Action, Controlling). So Islamic Education Institutions must have a proven strategy for creating POAC in developing human resources well, including: 1) creating a planning design; 2) the existence of a teaching staff development program; 3) implement the planned program; 4) carry out process evaluation. The process of developing human resources in Islamic Education Institutions has at least four phases, including: 1) Diagnostic Phase; 2) Design Phase; 3) Implementation Phase; 4) Evaluation Phase. The strategies and phases above need to be passed by Islamic Education Institutions with the aim of being able to lead each Islamic Education Institution towards improvement and improvement of superior quality and achievement.